(untitled) (قضايا سياسية, 2024)
Since the end of the Cold War, the cultural and political discourse has witnessed many concepts that have crystallized, spread and spread within the framework of the changes in the prevailing concepts known to the world, the most important of which is the concept of rebuilding the state, especially in the post-conflict phase, which has gained more importance in light of the major changes and transformations that the world has witnessed in the past few years, and in light of the new connotations that it has acquired, a great circulation of this concept has emerged in the Arab world, especially after the occupation of Iraq in 2003 and the spread of waves of popular uprisings in 2011. And the collapse of the ruling political regimes, which in turn led to the collapse of state institutions with them, including the Libyan, Syrian, Yemeni and finally Sudanese cases.